ʼBri guṅ thel chos Bdud rtsiʼi thigs pa : a collection of highly esoteric instructions on various aspects of Buddhist practice, comprising the "sealed" or bkaʼ-rgya-ma portions of the collected writings (gsuṅ-ʼbum) of ʼbri-guṅ Skyob-pa ʼJig-rten-mgon-po - ʼBri-guṅ Chos-rje ʼJig-rten-mgon-po, 1143-1217 (Gedan sungrab minyam gyunphel series, 1975)
Esoteric texts of the Drikung Kargyudpa tradition of Tibetan Lamaism.